-25-3x=-7(x+6)

Simple and best practice solution for -25-3x=-7(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25-3x=-7(x+6) equation:



-25-3x=-7(x+6)
We move all terms to the left:
-25-3x-(-7(x+6))=0
We calculate terms in parentheses: -(-7(x+6)), so:
-7(x+6)
We multiply parentheses
-7x-42
Back to the equation:
-(-7x-42)
We get rid of parentheses
-3x+7x+42-25=0
We add all the numbers together, and all the variables
4x+17=0
We move all terms containing x to the left, all other terms to the right
4x=-17
x=-17/4
x=-4+1/4

See similar equations:

| y-1/2=-3/5 | | 7x-9.64=5x2.32 | | -1,5q^2+6q+2,5=0 | | 6+3(y-4)=-3y | | 1/2n+3=4 | | 3=2y+1 | | (-8x+5)(-2-3x)=0 | | x+3/4=1/8 | | -0,5q^2+6q+12,5=0 | | 0.2n+9=7(0.4n-1) | | 12x+9=-27 | | 7(2n=3) | | 20y=2y-1 | | 7.1-2x=6.1 | | 2x-6+-5x=3(-x+7) | | 11.97+x=5x-0.11 | | 7+3(x=2= | | 0.23x-4.2=0.55x+7.2-x | | .5x-3=6 | | v+7/8=-1/2 | | 3m+3=15m= | | 2x+18=51 | | 1/4z-9=1 | | u+3.9=9.11 | | x+1/4=-5/8 | | 45=3w+12 | | 6x+100x=18*50 | | 2n12=82 | | =32−2u | | 2^(2x)=1000 | | 1000=2^2x | | x=x+19 |

Equations solver categories